Relationship between accelerometer-measured physical activity and depressive symptoms in hemodialysis patients with comorbid diabetes mellitus: a multicenter cross-sectional study - Ruiting Liang; Ruiting Liang; Xiaoyu Chen; Gaowa Siqin; Zhixin Zhang; Zhixin Zhang; Shumei Zhang; Lihua Li; SarNa Talin; Qi Guo (Frontiers in Psychology)
ObjectiveThe objective of this study was to examine the association between accelerometer-derived moderate-to-vigorous physical activity (MVPA) and depressive symptoms in hemodialysis patients with and without type 2 diabetes mellitus (T2DM).MethodsThis cross-sectional study finally included 450 maintenance hemodialysis patients (male 281, average age 62 years) from seven dialysis centers in Shanghai, China. Physical activity (PA) was measured using the triaxial accelerometer (ActiGraph GT3X+, Pensacola, FL, United States). We measured depressive symptoms using the 9-item Patient Health Questionnaire (PHQ-9) (PHQ-9 ⩾ 10). We categorized physical activity into quartile groups (Q1 through Q4), with the first quartile defined as low engagement and the remaining quartiles defined as moderate to high engagement. We used logistic regression and trend test to analyze the relationship between quartile groups and depressive symptoms. The analyses in this study adjusted for a range of confounders.ResultsThe prevalence of depression was higher in patients with hemodialysis combined with T2DM (17.2%). In diabetic patients, MVPAQ4 was negatively associated with depression after adjusting for covariates [OR = 0.076; 95% confidence interval (CI) = 0.006–0.955, p = 0.046]. However, in non-diabetic hemodialysis patients, no significant association was found between MVPAQ1-Q4 and depression after adjusting for covariates (p > 0.05).ConclusionModerate-to-vigorous physical activity was associated with depression in the diabetic hemodialysis group, but not in the non-diabetic group. Further studies are needed to investigate more causal relationships between MVPA and depressive symptoms in patients with T2DM.